2017
DOI: 10.1136/bmjopen-2016-015783
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of propofol and dexmedetomidine infused overnight to treat hyperactive and mixed ICU delirium: a protocol for the Basel ProDex clinical trial

Abstract: Background/objectivesDelirium is a neurobehavioural disturbance that frequently develops particularly in the intensive care unit (ICU) population. It was first described more than half a century ago, where it was already discovered as a state that might come along with serious complications such as prolonged ICU and hospital stay, reduced quality of life and increased mortality. However, in most cases, there is still lack of proof for causal relationship. Its presence frequently remains unrecognised due to sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…The Ramsay scores of patients reach 2-4, and there was no statistically significant difference in sedation depth for the two drugs. In respect of the analgesic effect, studies have shown that dexmedetomidine can be safely used more than 72 h, significantly reducing the analgesic demand with 50%~70% compared with propofol [15,16]. Our results also show that the dexmedetomidine group required less analgesic than the midazolam group, so dexmedetomidine may have a certain degree of analgesic effect.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The Ramsay scores of patients reach 2-4, and there was no statistically significant difference in sedation depth for the two drugs. In respect of the analgesic effect, studies have shown that dexmedetomidine can be safely used more than 72 h, significantly reducing the analgesic demand with 50%~70% compared with propofol [15,16]. Our results also show that the dexmedetomidine group required less analgesic than the midazolam group, so dexmedetomidine may have a certain degree of analgesic effect.…”
Section: Discussionsupporting
confidence: 55%
“…The results suggested that after admission to ICU, the BPS score in dexmedetomidine group was slightly decreased, then kept at a low level, and was lower than that in the midazolam 60 participants assessed for eligibility 16 3 BioMed Research International group at T3-T5. There was no statistically significant difference between the two groups in other time points as indicated in Figure 3 3.5.…”
Section: Sedative Effect and Analgesic Effectmentioning
confidence: 92%
“…The results of our meta-analysis suggest that dexmedetomidine may be more efficient in reducing ICU delirium incidence than placebo standard sedatives and opioids. The evidence on treatment of ICU delirium with dexmedetomidine is limited, as only three trials with different comparators each were suitable for our investigation, and needs to be further investigated [ 66 ]. Additionally, it is necessary to standardize clinical outcomes in general, and especially in the treatment section to facilitate meta-analyses, thereby ensuring robust evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The administration of dexmedetomidine compared with propofol to treat disturbed circadian rhythm in the other two types of delirium-hyperactive and mixed-is being investigated in our counterpart study: The Basel ProDex clinical study-Comparison of propofol and dexmedetomidine infused overnight to treat hyperactive and mixed ICU delirium (Study Protocol, BMJ Open, July 2017). 16…”
Section: Open Access Background and Rationalementioning
confidence: 99%